2012
DOI: 10.1093/neuonc/nos155
|View full text |Cite
|
Sign up to set email alerts
|

Primary CNS germ cell tumors in Japan and the United States: an analysis of 4 tumor registries

Abstract: Intracranial germ cell tumors (GCTs) are relatively rare. Their incidence has been considered to be higher in East Asia than in the United States. This study estimates the incidence of CNS GCTs in Japan and the United States, investigates gender discrepancies in each country, and describes treatment outcomes. Data on primary CNS GCTs from 4 databases were utilized: population-based malignant incidence data from (1) the Japan Cancer Surveillance Research Group (2004-2006; 14 registries), malignant and nonmalign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
112
2
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(126 citation statements)
references
References 13 publications
7
112
2
5
Order By: Relevance
“…However, a recent analysis by McCarthy et al [6] showed that there was no statistically significant difference between Japan and the USA in the incidence rate of malignant GCTs. They reported that the rate for malignant GCTs documented by the Japan Cancer Surveillance Research Group (JCSRG: 2004-2006) was 0.096 (males: 0.143, females: 0.046) per 10 5 while the rate documented for the USA by the Surveillance, Epidemiology, and End Results Program (SEER: 2004-2008) was 0.075 (males: 0.118, females: 0.030) per 10 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent analysis by McCarthy et al [6] showed that there was no statistically significant difference between Japan and the USA in the incidence rate of malignant GCTs. They reported that the rate for malignant GCTs documented by the Japan Cancer Surveillance Research Group (JCSRG: 2004-2006) was 0.096 (males: 0.143, females: 0.046) per 10 5 while the rate documented for the USA by the Surveillance, Epidemiology, and End Results Program (SEER: 2004-2008) was 0.075 (males: 0.118, females: 0.030) per 10 5 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the incidence of some types of tumor is different in different ethnic populations. For example, the incidence of GCTs has been reported to be higher in Orientals than Westerners [3,4,5], although a 2012 analysis of 4 tumor registries in Japan and the USA found no statistically significant difference [6]. While most CNS-GCTs are seen in patients aged between 10 and 19 years of age [7], the percentage in children aged between 0 and 14 years ranged from 35.3 to 41.5% in these registries.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of patients (60-70%) are <20 years old, and 53% of patients are between 10 and 19 years old at the point of diagnosis. The disease is rare in patients >35 years old (4).…”
Section: Discussionmentioning
confidence: 99%
“…A recent report showed that Japan and the United States share a similar incidence of primary germ cell tumors, exhibiting the same genderbased patterns. [5] Primary IGCTs are usually located either in the suprasellar or pineal regions. [6] According…”
Section: Introductionmentioning
confidence: 99%